Engineering of L-amino acid deaminases for the production of α-keto acids from L-amino acids - Nshimiyimana, Project (Bioengineered, 2019)
α-keto acids are organic compounds that contain an acid group and a ketone group. L-amino acid deaminases are enzymes that catalyze the oxidative deamination of amino acids for the formation of their corresponding α-keto acids and ammonia. α-keto acids are synthesized industrially via chemical processes that are costly and use harsh chemicals. The use of the directed evolution technique, followed by the screening and selection of desirable variants, to evolve enzymes has proven to be an effective way to engineer enzymes with improved performance. This review presents recent studies in which the directed evolution technique was used to evolve enzymes, with an emphasis on L-amino acid deaminases for the whole-cell biocatalysts production of α-keto acids from their corresponding L-amino acids. We discuss and highlight recent cases where the engineered L-amino acid deaminases resulted in an improved production yield of phenylpyruvic acid, α-ketoisocaproate, α-ketoisovaleric acid, α-ketoglutaric acid, α-keto-γ-methylthiobutyric acid, and pyruvate.